Miller's still for the distillation of alcohol (Encyclopædia of Chemistry, Theoretical, Practical, and Analytical, as Applied to the Arts and Manufacturers, Vol. I and II, 1877)
Still patented by James Miller for the distillation of alcohol.
Keywords: Distillation apparatus; Chemistry, Technical